P.046 Multiple intracranial mycotic aneurysms and management dilemma in postinterventional cerebral vasospasm: a case report. (2nd June 2017) - Al Jishi, AA; Takroni, R; Whittingham, H; Meade, M; Freitag, A; Van Adel, B
Abstract : Background: Intracranial mycotic aneurysms are rare forms of vascular abnormalities. They are typically fragile and have high tendency to bleed. Even when they are successfully secured upon intervention, the medical management can be challenging in presence of other non-ruptured aneurysms and concomitant cerebral vasospasm.Methods: A 31 year old female was admitted with right sided large intracerebral hemorrhage due to ruptured mycotic MCA aneurysm. She was also known with severe tricuspid regurgitation from drug abuse. Others aneurysms were also located intracranially and extracranially, including subclavian and renal arteries.Results: The MCA aneurysm was successfully clipped during decompressive craniectomy. The non-ruptured left ACA aneurysm was occluded through endovascular intervention. Due to cardiac condition and presence of other non-secured extarcranial aneurysms, we followed the MNI protocol for treating cerebral vasospsam by milrinone infusion. The treatment was successful for over three weeks until another micro-aneurysm had ruptured which had lead to severe and rapid clinical deterioration, that had lead eventually to death.Conclusions: Intracranial mycotic aneurysms remain challenging. Patients should be selected for surgical clipping versus endovascular intervention based on clinical state and radiological features. We suggest using milrinone over induced hypertension therapy for post-intervention cerebral vasospasm in order to lower the risk for rupturing non-secured aneurysms.